(untitled) (International Seven Journal of Multidisciplinary, 2026)
Congenital hearing loss affects approximately 1 to 2 per 1,000 live births, with more than 50% of cases presenting a hereditary etiology. Early recognition of these causes, combined with effective neonatal hearing screening through Transient Evoked Otoacoustic Emissions (TEOAE) and Automated Auditory Brainstem Response (AABR), allows not only timely detection of hearing impairment but also etiological characterization, with a direct impact on therapeutic decision-making, functional prognosis, and family counseling. In this context, advances in molecular genetics and the development of gene therapies have emerged as promising perspectives for the future treatment of monogenic forms of congenital hearing loss (Mey et al., 2025; Lieu et al., 2020; Taylor et al., 2021). Without appropriate treatment, congenital hearing loss can lead to deficits in the development of communication, behavior, and intellect (Lieu et al., 2020; Zhang et al., 2025). Considering this, the identification of congenital hearing loss through Transient Evoked Otoacoustic Emissions (TEOAE) and Automated Auditory Brainstem Response (AABR) in neonatal hearing screening programs is crucial to initiate early rehabilitation with hearing aids or cochlear implants (Mey et al., 2025).